Cold Atmospheric Plasma Is a Promising Alternative Treatment Option in Case of Split Skin Graft Failure - Aydar Khabipov; Andre Schreiber; Stephan Kersting; Richard Hummel; Johannes Höhn; Lars-Ivo Partecke; Sander Bekeschus; Anne Glitsch; Wolfram Keßler (Case Reports in Surgery, 2024)
Cold atmospheric plasma (CAP) has shown promising potential in promoting wound healing. This case report presents the successful application of CAP in a 42-year-old female patient with extensive wound healing disorders and superinfections following the excision of an abscess in the left thoracic region. After several failed split skin graft attempts, the implementation of CAP led to significant improvements in wound healing. This report highlights the wound healing-promoting effects of CAP and discusses its potential mechanisms of action.